Synbiotics as a novel therapeutic approach for hyperphosphatemia and hyperparathyroidism in chronic kidney disease rats - Anegkamol, Weerapat; Bowonsomsarit, Wirin; Taweevisit, Mana; Tumwasorn, Somying; Thongsricome, Thana; Kaewwongse, Maroot; Pitchyangkura, Rath; Tosukhowong, Piyaratana; Chuaypen, Natthaya; Dissayabutra, Thasinas (Scientific reports, 2025)
Hyperphosphatemia and secondary hyperparathyroidism (SHPT) are the common complications found in CKD that lead to severe complications including mineral bone disease (MBD), vascular calcification (VC), and cardiovascular mortality. To mitigate hyperphosphatemia, SHPT and uremic toxemia, we supplemented cisplatin-induced CKD rats with a synbiotic composed of Lactobacillus salivarius LBR228, Bifidobacterium longum BFS309, fructo-oligosaccharide and chitosan oligosaccharide, with Lactobacillus casei as a standard probiotic control. After the 12 weeks experiment, rats supplemented with the synbiotic had lower serum phosphate, calcium-phosphorus product, serum parathyroid hormone, and indoxyl sulfate levels than untreated rats. The expression of type 1 RNA and protein expression were increased in rats treated with the synbiotics. Our result showed that synbiotic treatment alleviates hyperphosphatemia and SHPT, which are the main risks of MBD and VC. The mode of the synbiotic action is hypothesized to associate with the improvement of the tight junction and gut barrier, leading to the suppression of intestinal paracellular phosphate transport. This study demonstrated the beneficial effects of synbiotic treatment in the control of serum phosphate and parathyroid hormone in an animal model with CKD.